pH-cycling Model to Verify the Efficacy of Fluoride-releasing Materials in Enamel Demineralization - Rodrigues, E. [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Pedrini, Denise [UNESP]; Oliveira, M. S. R. (Operative Dentistry Inc, 2008)
The current study proposes a pH-cycling model to verify the dose-response relationship of fluoride-releasing materials in their ability to reduce in vitro demineralization. Sixty bovine enamel blocks (4 x 3 x 3 mm) were selected, using baseline surface microhardness (SMH1) evaluations at different distances from the enamel sectioned border (150, 300, 450 and 600 pm). Specimens (n=48) were prepared with Z100, Fluroshield and Vitremer at the standard powder/liquid ratio and at a 1/4 diluted-powder/liquid ratio. The 12 remaining specimens were used as a control group. The specimens were submitted to a pH-cycling model with high cariogenic challenge. After pH-cycling, final surface microhardness (SMH2) was assessed to calculate the percentage change of surface microhardness (%SMHc). Next, the fluoride present in enamel (mu g F/mm(3)) and in pH-cycling solutions (mu g F) was measured. Cross-sectional microhardness was done to calculate the mineral content (Delta Z). Data from %SMHc, Delta Z and mu g F were analyzed by analysis of variance (p<0.05), while mu g F/mm(3) analysis was done using the Kruskal-Wallis test. The results showed a correlation between %SMHc and mu g F/mm(3) (r(2)=0.4129; p<0.0001), %SMHC and mu g F (r(2)=0.4932; p<0.0001), Delta Z and mu g F/mm(3) (r(2)=0.4573; p<0.0001), mu g F/mm(3) and mu g F (r(2)=0.3029; p<0.0001) and between Delta Z and mu g F (r(2)=0.5276; p<0.0001). The pH-cycling model allowed the in vitro verification of the dose-response relationship of fluoride-releasing materials in the demineralization of enamel.